Effectiveness and Cost-Effectiveness of Sequential Treatment of Patients with Chronic Myeloid Leukemia in the United States: A Decision Analysis. (10th December 2015) - Rochau, Ursula; Kluibenschaedl, Martina; Stenehjem, David; Kuan-Ling, Kuo; Radich, Jerald; Oderda, Gary; Brixner, Diana; Siebert, Uwe
Abstract : Currently several tyrosine kinase inhibitors (TKIs) are approved for treatment of chronic myeloid leukemia (CML). Our goal was to identify the optimal sequential treatment strategy in terms of effectiveness and cost-effectiveness for CML patients within the US health care context. We evaluated 18 treatment strategies regarding survival, quality-adjusted survival, and costs. For model parameters, the literature data, expert surveys, registry data, and economic databases were used. Evaluated strategies included imatinib, dasatinib, nilotinib, bosutinib, ponatinib, stem-cell transplantation (SCT), and chemotherapy. We developed a Markov state-transition model, which was analyzed as a cohort simulation over a lifelong time horizon with a third-party payer perspective and discount rate of 3%. Remaining life expectancies ranged from 5.4 years (3.9 quality-adjusted life years (QALYs)) for chemotherapy treatment without TKI to 14.4 years (11.1 QALYs) for nilotinib→ dasatinib→ chemotherapy/SCT. In the economic evaluation, imatinib→ chemotherapy/SCT resulted in an incremental cost-utility ratio (ICUR) of 171, 700/QALY compared to chemotherapy without TKI. Imatinib→ nilotinib→ chemotherapy/SCT yielded an ICUR of 253, 500/QALY compared to imatinib→ chemotherapy/SCT. Nilotinib→ dasatinib→ chemotherapy/SCT yielded an ICUR of 445, 100/QALY compared to imatinib→ nilotinib→ chemotherapy/SCT. All remaining strategies were excluded due to dominance of the clinically superior strategies. Based on our analysis and current treatment guidelines, imatinib→ nilotinib→ chemotherapy/SCT and nilotinib→ dasatinib→ chemotherapy/SCT can be considered cost-effective for patients with CML, depending on willingness-to-pay.